2014
DOI: 10.1253/circj.cj-14-0521
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Receptor Agonist, FTY720, Restores Coronary Flow Reserve in Diabetic Rats

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp vasomotor function. 12-14 By using PET with 13 N-ammonia, it is possible to measure myocardial perfusion in a non-invasive way and quantify myocardial blood flow (MBF) in a resting and pharmacologic stress phase with adenosine or dipyridamole (hyperemic response). 15 The use of 13 N-ammonia for quantification of MBF has been compromised by the non-linear relationship between tracer tissue retention and myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…S1P agonists FTY720 and KRP-203 dramatically attenuate the development of atherosclerosis in ApoE KO mice and LDL receptor KO mice (97). FTY720 has also been shown to improve the coronary dysfunction and restore the reduced coronary flow reserve in diabetic rats (100). …”
Section: S1p Signaling In Vasculaturementioning
confidence: 99%
“…S1P agonists FTY720 and KRP-203 dramatically attenuate the development of atherosclerosis in ApoE KO mice and LDL receptor KO mice (97). FTY720 has also been shown to improve the coronary dysfunction and restore the reduced coronary flow reserve in diabetic rats (100). …”
Section: S1p Signaling In Vasculaturementioning
confidence: 99%
“…According to literature, S1P receptor agonists have an important role in immune suppression (Luessi et al, 2015). Various experimental models have been used to test for including a porcine model of I/R (Santos-Gallego et al, 2016) and spontaneous obstructive coronary atherosclerosis murine model (Xu et al, 2014). Using these models, a reduction in infarct size and low mortality have been shown in the FTY720-treated groups.…”
Section: Discussionmentioning
confidence: 99%
“…S1P receptor agonists have important roles in immune suppression [39]. A porcine model of I/R [17] and a spontaneous obstructive coronary atherosclerosis murine model [40] tested for immunosuppression, showed reduction in infarct size and mortality in the fingolimod-treated group. In the present study, a significantly lower concentration of pro-inflammatory cytokines was found in blood and tissues subjected to inflammation, a finding concordant with the previous data [40].…”
Section: Discussionmentioning
confidence: 99%